Effect of T6 Tempering on the Wear and Corrosive Properties of Graphene and B4C Reinforced Al6061 Matrix Composites - Bharathiraja Parasuraman; Anthony Xavior Michael (Journal of Manufacturing and Materials Processing)
This research study aims to evaluate the wear and corrosive behaviour of aluminum 6061 alloy hybrid metal matrix composites after reinforcing them with graphene (0.5, 1 wt.%) and boron carbide (6 wt.%) at varying weight percentages. The hybrid composites were processed through ball milling and powder compaction, followed by a microwave sintering process, and T6 temper heat treatment was carried out to improve the properties. The properties were evaluated and analyzed using FE-SEM, Pin-on-Disc tribometer, surface roughness, salt spray test, and electrochemical tests. The results were evaluated prior to and subsequent to the T6 heat-treatment conditions. The T6 tempered sample S1 (Al6061-0.5% Gr-6% B4C) exhibits a wear rate of 0.00107 mm3/Nm at 10 N and 0.00127 mm3/Nm at 20 N for 0.5 m/s sliding velocity. When the sliding velocity is 1 m/s, the wear rate is 0.00137 mm3/Nm at 10 N and 0.00187 mm3/Nm at 20 N load conditions. From the Tafel polarization results, the as-fabricated (F) condition demonstrates an Ecorr of −0.789 and an Icorr of 3.592 µA/cm2 and a corrosion rate of 0.039 mm/year. Transitioning to the T6 condition further decreases Icorr to 2.514 µA/cm2, Ecorr value of −0.814, and the corrosion rate to 0.027 mm/year. The results show that an increase in the addition of graphene wt.% from 0.5 to 1 to the Al 6061 alloy matrix deteriorated the wear and corrosive properties of the hybrid matrix composites.